Manufacturing‐dependent change in biological activity of the TLR4 agonist GSK1795091 and implications for lipid A analog development. Issue 11 (12th September 2022) - Steeghs, Neeltje; Hansen, Aaron R.; Hanna, Glenn J.; Garralda, Elena; Park, Haeseong; Strauss, James; Adam, Michael; Campbell, Gossett; Carver, Jennifer; Easton, Rachael; Mays, Katherine; Skrdla, Peter; et al.
Abstract: A phase I trial (NCT03447314; 204686) evaluated the safety and efficacy of GSK1795091, a Toll‐like receptor 4 (TLR4) agonist, in combination with immunotherapy (GSK3174998 [anti‐OX40 monoclonal antibody], GSK3359609 [anti‐ICOS monoclonal antibody], or pembrolizumab) in patients with solid tumors. The primary endpoint was safety; other endpoints included efficacy, pharmacokinetics, and pharmacodynamics (PD). Manufacturing of GSK1795091 formulation was modified during the trial to streamline production and administration, resulting in reduced PD (cytokine) activity. Fifty‐four patients received GSK1795091 with a combination partner; 32 received only the modified GSK1795091 formulation, 15 received only the original formulation, and seven switched mid‐study from the original to the modified formulation. Despite the modified formulation demonstrating higher systemic GSK1795091 exposure compared with the original formulation, the transient, dose‐dependent elevations in cytokine and chemokine concentrations were no longer observed (e.g., IP‐10, IL10, IL1‐RA). Most patients (51/54; 94%) experienced ≥1 treatment‐emergent adverse event (TEAE) during the study. Safety profiles were similar between formulations, but a higher incidence of TEAEs associated with immune responses (chills, fatigue, pyrexia, nausea, and vomiting) were observed with the original formulation. No conclusions can be made regarding GSK1795091 anti‐tumor activity due to the limited data collected. Manufacturing changes were hypothesized to have caused the change in biological activity in this study. Structural characterization revealed GSK1795091 aggregate size in the modified formulation to be twice that in the original formulation, suggesting a negative correlation between GSK1795091 aggregate size and PD activity. This may have important clinical implications for future development of structurally similar compounds.